The Philippines and al-Andalus linking the edges of the classical Islamic world - Donoso, Isaac (Philippine studies : historical and ethnographic viewpoints, 2015)
"This research note offers a broad analysis of the central elements that constitute Islamic identity in the Philippines in a manner that reconciles Philippine Islam with the global history of Islamic civilization. The contact with the Spaniards and the legacy of Islamic Spain serve as essential elements in defining Islamicity in the Philippines. Hence, Islam in the Philippines can be appreciated as combining the richness of a cultural process that includes influences from the EAst as well as the West (al-Andalus), shaping the Philippines as the meeting place of both edges of the Islamic world."